2019
DOI: 10.1186/s12881-019-0831-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between methylenetetrahydrofolate reductase C677T polymorphism, HPV infection and cervical intraepithelial neoplasia in Brazilian women

Abstract: Background: Cervical cancer has high prevalence and mortality rates in worldwide female population. Persistent infection by high-risk Human Papillomavirus (hr-HPV) is the main cause of this cancer. However, many environmental, genetical, and epigenetical cofactors can modulate viral infection and cervical carcinogenesis. Methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism is a genetic factor that has been associated with many pathologies, including cancer. Nevertheless, studies with cervical cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…2 , 12 Samples from forty women with BV detected by the Gram staining and forty women without BV were randomly selected and submitted for Trichomonas vaginalis (T. vaginalis), Neisseria gonorrhoeae (N. gonorrhoeae), Chlamydia trachomatis (C. trachomatis) and Human Papilloma Virus (HPV) detection by Polymerase Chain Reaction (PCR). 3,17,18 Databases were generated using EpiData version 3.2 (EpiDataAssociation, Odense, Denmark) by double entry of the results, and they were subsequently compared, corrected, and analyzed using STATA version 14.0 software (Stata Corp., College Station, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…2 , 12 Samples from forty women with BV detected by the Gram staining and forty women without BV were randomly selected and submitted for Trichomonas vaginalis (T. vaginalis), Neisseria gonorrhoeae (N. gonorrhoeae), Chlamydia trachomatis (C. trachomatis) and Human Papilloma Virus (HPV) detection by Polymerase Chain Reaction (PCR). 3,17,18 Databases were generated using EpiData version 3.2 (EpiDataAssociation, Odense, Denmark) by double entry of the results, and they were subsequently compared, corrected, and analyzed using STATA version 14.0 software (Stata Corp., College Station, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This study shows that out of a total of 107 women with a lesion of the cervix, 50 of them have intraepithelial neoplasms of the cervix, a frequency of 46.7%. In the study of intraepithelial neoplasia of the cervix in Brazilian women, the authors found 90 cases of intraepithelial neoplasias in 150 cervical samples, or 60% of cases [50]. Mwenze et al, in a study carried out in Lubumbashi on screening for cervical cancer in the population, observed a frequency of intraepithelial neoplasia of the cervix equal to 13% within the population of Lubumbashi [51].…”
Section: Frequency Of Intraepithelial Neoplasiamentioning
confidence: 99%
“…Although intraepithelial neoplasia is the most common lesions of the cervix [60]. Their proportions are much greater when the studies concern patients with clinically identifiable lesions [50]. But in cases where studies are done to screen a population for cervical cancer, the frequencies of intraepithelial neoplasms are relatively low [21].…”
Section: Frequency Of Intraepithelial Neoplasiamentioning
confidence: 99%
“…The distribution of polyps, namely colorectal polyps which were more common in the left side of the colon than the right side, follows and parallels the distribution of colorectal cancer (48). Further study is needed to examine genome-wide association studies to identify candidate genes (49) and polymorphism (50)(51)(52) in different populations.…”
Section: Age Groupmentioning
confidence: 99%